The association between quantitative workload, person-job fit, and career sustainability among Ukrainian hidden expatriates in Czechia - Soudil, Dominik Nicolas (My University, 2026)
Following the Russian invasion of Ukraine in 2022, an unprecedented wave of Ukrainian citizens has entered the Czech labour market. Despite many of them possessing robust levels of human capital and advanced educational or career backgrounds, systemic and institutional barriers have structurally pushed many of the highly skilled professionals into low-status, physically demanding employment roles. This forced occupational displacement has led to the emergence of a highly vulnerable workforce demographic conceptualised as "hidden expatriates." Unlike traditional expatriates, who may benefit from extensive organisational support or utilisation of their professional skills, these individuals may frequently face severe underemployment and possibly a profound "brain waste" phenomenon. Anchored in the sustainable careers framework and supported by the job demands-resources (JD-R) model, this thesis empirically examines the career sustainability of this specific expatriate group. Specifically, the research aims to investigate how two primary work-related antecedents, namely quantitative workload and person-job fit, may be associated with the core career sustainability indicators. These indicators include health (measured through job exhaustion), happiness (evaluated via subjective career success) and productivity (assessed through perceived internal and external marketability). To address these objectives, a quantitative, cross-sectional research design is employed. Primary data has been collected via a digital survey from a non-probability sample of 103 Ukrainian hidden expatriates who are currently employed in manual, service, or entry-level roles in Czechia. By focusing strictly on these demanding employment roles, the research strives towards uncovering possible mechanisms threatening this displaced workforce. The collected data is then analysed using multiple linear regression analyses to test the theoretical hypotheses. The findings suggest that quantitative workload is positively associated with job exhaustion and negatively associated with subjective career success and internal marketability. Person-job fit, in contrast, is positively associated with subjective career success and perceived marketability, and negatively associated with job exhaustion. These results indicate that demanding work con-ditions and the underutilisation of workers’ skills may be important factors in understanding the career sustainability of Ukrainian hidden expatriates in Czechia. Finally, this study aims to contribute to the international human resource management (IHRM) literature by applying the sustainable career lens to a frequently overlooked expatriate group. The thesis highlights a possible managerial need for host-country employers and policymakers to implement systemic changes. It is argued that by actively mitigating work requirements resulting in high quantitative workload and proactively utilising the latent human capital of displaced workers, organisations may prevent workforce degradation and support a more sustainable career ecosystem within the researched demographic group.
Keywords: know-how; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business